2020
DOI: 10.32615/ps.2020.058
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and selenium as modulating factors of the anatomy and physiology of Billbergia zebrina (Bromeliaceae) during in vitro culture

Abstract: Deleterious effects induced by high zinc (Zn) concentrations can be alleviated with selenium (Se) co-exposure. Therefore, we analyzed the morphophysiological changes of Billbergia zebrina in response to Zn and Se co-exposure. Plants were cultured in media containing three Zn concentrations (0, 30, and 300 μM) combined with two Se concentrations (0 and 4 μM), for a total of six treatments. At 75 d of culture, the leaf anatomy, chlorophyll (Chl) a fluorescence, and contents of photosynthetic pigments (Chl) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…An increase of V I may indicate partial inhibition on the acceptor side of PSII due to a relative change in the QB-nonreducing PSII RCs (Jiang et al 2008). It can result in a lower efficiency/probability of electron movement from PSII to the PSI acceptor side (Martins et al 2020b). Therefore, the decreased values of VI, verified in this work, corresponded to a relative improvement of electron transport to PSI, which was reflected in increased values of ψR0 and φR0.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…An increase of V I may indicate partial inhibition on the acceptor side of PSII due to a relative change in the QB-nonreducing PSII RCs (Jiang et al 2008). It can result in a lower efficiency/probability of electron movement from PSII to the PSI acceptor side (Martins et al 2020b). Therefore, the decreased values of VI, verified in this work, corresponded to a relative improvement of electron transport to PSI, which was reflected in increased values of ψR0 and φR0.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, the A. imperialis plants had φP0 values greater than 0.78, meaning there was no sign of photoinhibition at 56 d of growth, irrespective of Se treatments. Besides no changes in these parameters, the plants also had similar values of W L, VK, FK/FJ, FV/F0, and WK, together denoting no damage to the functional and structural integrity of the thylakoid membranes and in the oxygen-evolving complex (OEC) (Oukarroum et al 2009, Zhang et al 2018, Faseela et al 2020, Martins et al 2020b.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Various methods have been employed to minimize the effects of Cd contamination of ecosystems, ranging from the use of physical-chemical methods to the use of living organisms, such as plants, bacteria, and fungi that can extract and store high concentrations of this metal in their structure (Liu et al 2018;Roychowdhury et al 2018;Haider et al 2021). Besides this, studies have shown that the cultivation of plants with the presence of stress-mitigating elements such as selenium (Se) and silicon (Si) is promising to diminish the deleterious effects of trace elements on the plants' systems (Ding et al 2017; Martins et al 2020a;Haider et al 2021;Huang et al 2021). However, more comprehensive studies are necessary to understand better the relationship among plants, heavy metals, and stress-mitigating elements to ascertain whether this mitigation is really feasible as part of a strategy for the recovery of ecosystems.…”
Section: Introductionmentioning
confidence: 99%